Gender Differences in the Quality of Life of Patients with Liver Cirrhosis (Journal of Fatima Jinnah Medical University, 2024)
ABSTRACTChronic liver disease frequently arises as a consequence of hepatitis C virus (HCV) infection, which can have detrimental effects on the quality of life for those affected. Gender may play a significant role in assessing the disease's severity and managing it. Therefore, this study was conducted to see the gender-based difference in HRQoL among patients.Patient and Methods: A cross-sectional study was conducted at the Gastroenterology Department of Jinnah Hospital, Lahore . The study involved a total of 250 patients diagnosed with liver cirrhosis. To assess Health-Related Quality of Life (HRQoL), the researchers utilized the Chronic Liver Disease Questionnaire (CLDQ), which is a liver disease-specific questionnaire containing 29 items categorized into six domains. Each domain is assigned summary ratings ranging from 1 to 7, with higher scores indicating a lesser degree of impairment in HRQoL. The data were analyzed using SPSS version 25.0. Gender-based comparisons of CLDQ domains were made through an independent sample t-test.Results: In this study, total 250 patients were enrolled, 141 (56.4%) being male and 109 (43.6%) being female. The mean age of the patients was 49.52 ± 1.62. The assessment of the patients' liver condition using the Child-Pugh Class revealed that the majority, specifically 118 (47.2%) patients, were categorized as Class B. Within this group, 55 (39.0%) were male, and 63 (57.8%) were female. It was found that females tended to have a less impaired quality of life compared to males (Male=3.26 ± 0.81, Female=5.24 ± 1.02), and this difference was statistically significant. Furthermore, in the domain of fatigue (Male=2.93 ± 1.22, Female=3.05 ± 0.94) and emotional functioning (Male=3.31 ± 0.98, Female=5.04 ± 1.18), there were significant differences in the scores. Notably, males had better scores in the fatigue and emotional functioning as compared to females..Conclusion: These findings demonstrated that the gender variable's significant impact on HRQoL of CLD patients. It was found that females tended to have a less impaired quality of life compared to males. Males had better scores in the fatigue and emotional functioning as compared to female.
Keywords: Gender; HRQL; CLDQ